DEVELOPMENT OF INNOVATIONS IN THE EDUCATIONAL ENVIRONMENT: INCLUSIVE EDUCATION AND DIGITAL TECHNOLOGIES - Gogiberidze, George; Isakov, Vladimir; Ershova, Tamara; Shulgina, Olga (Revista Inclusiones, 2019)
The introduction of digital technologies in the educational process makes it possible to personify the presentation of numerical and graphical information, individually select the pace of learning, make the process of assessing competencies objective and increase the level of methodological support of the educational process. The use of the latest digital technologies in the planning of studentcentered inclusive education allows releasing the time reserves of teachers and ensuring the comfort of the implementation of routine processes. The purpose of this work is to analyze the characteristics of student-centered learning relative to the needs of students studying inclusively.